Predicting the effects of capping contaminated sediments via numerical simulations - Bortone, Imma; Di Natale, M.; Musmarra, D. (Taylor and Francis, 2018)
Contaminated sediments are one of the key risks to human health and the environment, due to high concentrations of many types of substances contained in them and their direct contact with the aquatic fauna. This contributes to fish consumption advisories and limits the uses of many water bodies. In this study, an in situ capping (ISC) is considered as a potential remedy to minimise the exposure of aquatic ecosystems to sediment contaminants and a valid alternative to ex situ remediation options, by reducing contaminant fluxes to the upper water. Numerical design simulations, taking into account a biosorptive sediment cap and comparing different adsorptive characteristics of sediments, are proposed. As a case study, polychlorinated biphenyls contaminated sediments of Lake Hartwell, an artificial lake located in South Carolina, USA, were considered. A numerical predictive model of concentrations in a multilayered bed sediment and overlying water was developed in order to evaluate the long-term effectiveness of ISC of different thicknesses. Results showed that, for the case study, a minimum 20 cm cap allows to reduce the contaminant flux to the overlying water through reaction of the contaminants with the capping matrix, by highlighting how sediment biosorptive characteristics can influence the cap design.
Keywords: Sediment capping; Contaminated sediments; Contaminant transport; Reactive transport; Flow modelling